Analysis of Student Errors in Solving Differential Calculus Problems on Absolute Inequalities and Functions Continuity - Supriyatin, Titin; Syafa’atun (Journal of Mathematics Education and Science, 2025)
his study aims to analyze the errors made by students in solving differential calculus problems, particularly in the topics of absolute value inequalities and the continuity of functions. The research involved 64 students from the Biology Education Program at Universitas Indraprasta PGRI who were enrolled in a differential calculus course during the spring semester of the 2024/2025. The research method employed was a descriptive qualitative approach with error analysis. Data was collected by administering differential calculus problems involving absolute value inequalities and function continuity, which were then analyzed based on the types of errors made by the students. By using radatz  the Error Analysis Theory , that The results showed that the errors made by students could be categorized into two main types: conceptual errors and computational errors. Conceptual errors included a lack of understanding in applying the definition of absolute value inequalities in certain cases, as well as difficulties in identifying points of discontinuity in functions. Computational errors were related to inaccuracies in performing differential calculations and in applying basic calculus theorems related to function continuity. These findings highlight the need for a more comprehensive teaching approach to strengthen students' understanding of fundamental theory and technical skills, as well as the importance of diverse problem-solving practice to reduce errors in concept application. This study is expected to contribute to the development of more effective strategies for teaching differential calculus among students.